THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE WRITING PRACTICES OF SIXTH-SEMESTER ENGLISH STUDENTS AT UIN SJECH M. DJAMIL DJAMBEK BUKITTINGGI - Dani Ramanda; Absharini Kardena; Eliza; Widya Syafitri (Universitas Mahaputra Muhammad Yamin, 2026)
Artificial Intelligence tools such as ChatGPT, Grammarly, and QuillBot are increasingly used in academic writing and offer both benefits and challenges for EFL learners. While these tools can support language development, concerns remain regarding students’ independence and academic integrity. This study examines the use of AI across different stages of writing and explores its perceived benefits and limitations among sixth semester English students at UIN Sjech M. Djamil Djambek Bukittinggi. A mixed methods convergent design was employed. Quantitative data were collected through a validated questionnaire from 88 students, while qualitative data were obtained from in depth interviews with 10 selected participants and analyzed thematically. The findings indicate that AI was widely used during pre writing and brainstorming (85 percent), drafting (92 percent), and revision (78 percent). Students reported improvements in grammar, organization, and vocabulary, with grammar receiving the highest mean score of 4.2 out of 5. However, 35 percent of participants admitted to copying AI generated content without proper paraphrasing, highlighting potential ethical concerns. The study emphasizes the importance of integrating digital literacy and ethical guidance in the use of AI for academic writing.